1998
DOI: 10.1111/j.1467-8624.1998.tb06190.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Word Learning by Fifteen‐Month‐Olds under Tightly Controlled Conditions

Abstract: Infants (12 to 17 months) were taught 2 novel words for 2 images of novel objects, by pairing isolated auditory labels with to‐be‐associated images. Comprehension was tested using a preferential looking task in which the infant was presented with both images together with an isolated auditory label. The auditory label usually, but not always, matched one of the images. Infants looked preferentially at images that matched the auditory stimulus. The experiment controlled within‐subjects for both side bias and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
234
2
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 215 publications
(257 citation statements)
references
References 33 publications
17
234
2
4
Order By: Relevance
“…The increased N200-500 cannot be due to differences in phonological familiarity because the novel-paired and novel-not-paired words were each heard the same number of times. Behavioral studies have shown that infants in this age range engage in fast mapping of word object pairings in as few as nine pairings (Woodward, Markman, & Fitzsimmons, 1994;Schafer & Plunkett, 1998). We cannot say definitively that the infants learned both new words.…”
Section: Discussionmentioning
confidence: 99%
“…The increased N200-500 cannot be due to differences in phonological familiarity because the novel-paired and novel-not-paired words were each heard the same number of times. Behavioral studies have shown that infants in this age range engage in fast mapping of word object pairings in as few as nine pairings (Woodward, Markman, & Fitzsimmons, 1994;Schafer & Plunkett, 1998). We cannot say definitively that the infants learned both new words.…”
Section: Discussionmentioning
confidence: 99%
“…If, however, children affixed the name to the part, they should either look equally to both objects (because both contained the part) or look significantly more at the part by itself. The tendency to look longer at a labeled object has been well established (Hollich et al, 1998;Schafer & Plunkett, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Because comprehension occurs automatically without time for reflection, it is important to examine listeners' interpretation during speech processing and not just afterward. When the preferential-looking methods used widely in infancy research were extended to studies of language comprehension, researchers began to use summary measures of looking time to assess infants' lexical knowledge (e.g., Golinkoff, Hirsh-Pasek, Cauley, & Gordon, 1987;Schafer & Plunkett, 1998). However, because processing efficiency was not their focus, studies using these techniques did not capture time-course information about speed of response as was standard in the adult literature.…”
Section: Efficiency In Speech Processing By Infantsmentioning
confidence: 99%